The Utilization of Glass Waste as Fine Aggregate Replacement and Rice Husk Ash as Cement Replacement in Concrete: A Review - Shahid Ali Shaikh Shaikh; Sajjad Ali Mangi; Muhammad Nawaz Sahito; Naveed Ayoub Ghumro; Faheem Ahmed Soomro (NAROTAMA UNIVERSITY, Indonesia, 2021)
Cement as a binder used in the mixture of concrete is a costly product and it is also harmful to the environment due to the emission of huge amounts of CO2 and other gases. Like cement the fine aggregate is also the main constituent of the concrete used as inert filler in concrete is also expensive. The researchers are probing towards the new inexpensive and environment friendly materials for the concrete. They have agreed over the point that by utilizing the recycled waste materials could be helpful in achieving the sustainable construction. So in this case a lot of research has been carried out for the utilization of rice husk ash as cement substitution and recycled waste glass as alternative of concrete fine aggregate. The outcome of this research is that these both green materials have enormous potential to contribute in the long-lasting handling of ineffectual solid waste, reduction of landfill sites, preserving natural resources and protecting atmosphere from extremely hazardous gases. The purpose of this review work is to summarize the previous research findings on utilization of rice husk ash and recycled waste glass as a substitution to the cement and fine aggregate respectively. This review paper will come up with the remarkable idea and valuable information for the upcoming researchers working for the aim of utilization of renewable and futile materials in the field of concrete technology.